Pendampingan Pengolahan Limbah Organik Menjadi Kompos Melalui Pengendalian Biaya Di Desa Kancinaa Kabupaten Buton - Nur Zarliani Uli; Dwi Agustyawati; Sania; Muh. Deswan (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Organic waste is one of the environmental challenges faced by rural communities, including Kancinaa Village, Buton Regency, where large amounts of organic waste are generated from agricultural, plantation, and household activities but remain underutilized due to limited processing skills and inadequate production cost management. This community service program aimed to enhance community capacity in converting organic waste into compost while improving understanding of production cost control. The methods employed included socialization, training, hands-on compost production practices, and continuous mentoring conducted in December 2025. The results indicated significant improvements in community knowledge and skills in compost production, productive utilization of organic waste, and efficient production cost management. The participatory approach proved effective in increasing environmental awareness and promoting sustainable waste management while strengthening the potential for rural economic self-reliance through the utilization of local resources.